Pre-harvest application of sodium alginate functionalized with melatonin enhances secondary metabolism in strawberry fruit - Georgiadou, Egli C.; García, Carlos J.; Taliadorou, Anna-Maria; Gedeon, Stella; Valanides, Nicolas; Varaldo, Alice; Gohari, Gholamreza; Balsells-Llauradó, Marta; Alcázar, Rubén; Hertog, Maarten L.A.T.M.; Tomás-Barberán, Francisco A.; Manganaris, George A.; et al. (My University, 2025)
The application of priming agents is a promising strategy to enhance the nutritional content of fruits and overall fruit quality. The current study aimed to assess the effect of the pre-harvest application of various priming agents [melatonin (Mel), sodium alginate (NaA), sodium alginate/melatonin conjugate (Mel-NaA), and putrescine dihydrochloride (Put)] on fruit quality attributes and secondary metabolite profile of a strawberry cultivar (Fragaria x ananassa Duchesne cv. ‘Felicity Q3’). The priming agents were directly applied on fruit at three successive developmental stages, namely large green (LG), small white (SW) and large white (LW). The use of Mel-NaA and Put showed promising results in improving fruit quality indicators (i.e. firmness, color), while Mel-NaA and putrescine-treated fruit were characterized by increased total flavonoid content. HPLC-DAD-ESI-MS/MS data showed variable regulation of flavan-3-ols, hydroxycinnamic acids, and conjugates contents by the different treatments, while ellagitannins and ellagic acid derivatives were significantly enhanced following Mel-NaA pre-treatment. Priming treatments did not result in the differential regulation of volatile organic compounds (VOCs) in comparison with controls, suggesting that primed fruit retain their aroma quality with no aroma profile ‘penalty’. In addition, molecular analysis revealed that fruit pre-treatment with the priming agents resulted in variable transcriptional regulation of known strawberry allergenic proteins, with the Mel-NaA treatment showing no significant effect. This ‘green’ approach holds promise for advancing our understanding of the effects of NaA as a smart delivery mechanism of chemical priming agents and its potential impact on the sustainable improvement of the physicochemical attributes of strawberries during the pre-harvest stage.
Keywords: Fragaria x ananassa; Phytochemicals; Ascorbic acid; Anthocyanin; Priming agents; Carrier; Allergenic proteins; Aroma